Assembling 2D van der waals heterostructures using motorized robotic system - Lim, Joseph Jun Wen (Nanyang Technological University, 2024)
Ever since the discovery of graphene in 2004, there has been a rapid development in the field of two-dimensional (2D) materials research. The wide availability of 2D materials has enabled the construction of 2D van der Waals heterostructures, which has revolutionized society. These heterostructures consist of a variety of properties that can be manipulated for applications in the energy storage, optoelectronics, and electronics industries. The original aim of this project was to leverage a motorized robotic system in the glovebox for assembling 2D van der Waals heterostructures with various 2D materials. These 2D materials include graphene, hexagonal boron nitride (hand), black phosphorus (BP), and indium selenide (InSe). However, due to issues with the glovebox and the time constraint of the project, the experiment was subsequently conducted under ambient conditions with the use of the regular 2D materials dry transfer station. The project involved the use of mechanical exfoliation using the Scotch tape exfoliation method and dry transfer techniques for the assembly of the 2D heterostructures. Since air-sensitive materials were being used, thicker layers of flakes for BP and InSe were selected for usage instead. The principle behind this action was that the protective oxide layer possessed by thicker flakes safeguards the flakes from further oxidation and contamination. The heterostructures constructed were then further examined and characterized for the application of photodetectors. The experiment results proved that there is immense potential for BP and InSe to perform together in a photodetector.